Dose optimisation for Loss of Response to Vedolizumab— Pharmacokinetics and Immune Mechanisms. (10th April 2021) - Ungar, Bella; Malickova, Karin; Hanžel, Jurij; Abu Arisha, Muhammad; Paul, Stephane; Rocha, Catia; Ben Shatach, Zohar; Abitbol, Chaya Mushka; Haj Natour, Ola; Selinger, Limor; Yavzori, Miri; Fudim, Ella; et al.
Abstract: Background: Real life data regarding pharmacokinetics of vedolizumab in patients needing dose optimisation are scarce. We set to examine whether pre-optimisation vedolizumab levels associate with therapy outcomes and which mechanisms explain the associations. Methods: A multicentre observational study assessed the outcome of dose increase in association with pre-escalation levels in vedolizumab-treated patients. SubsequentIy, α4β7 occupancy on peripheral blood [PB] and intestinal lamina propria [LP] tissues was investigated on various cellular subsets in patients undergoing lower endoscopy on infusion day. Cellular localisation of vedolizumab-bound α4β7 and effects on M1 and M2 macrophages were also explored. Results: A total of 161 inflammatory bowel disease [IBD] patients were included. Among 129/161 patients intensified during maintenance [Week 14 onward], pre-intensification trough levels were comparable or higher among those subsequently attaining post-optimisation clinical, biomarker, and endoscopic remission, compared with non-remitting patients [ p = 0.09, 0.25, 0.04, respectively]. Similar results were demonstrated for those dose-optimised during induction [Week 6, n = 32]. In the immune sub-study [ n = 43], free α4β7 receptors at trough were similarly low among patients with/without mucosal healing, on PB T cells [ p = 0.15], LP T cells [ p = 0.88], and on PB eosinophils [ p = 0.08]. Integrin receptors on M1 and M2 macrophages were also saturated by low levels of vedolizumab and anti-inflammatory cytokine secretion was not increased. Co-localisation and dissociation experiments demonstrated membranal α4β7 receptors of two origins: non-internalised and newly generated α4β7, but re-binding was still complete at very low concentrations. Conclusions: These results do not support pharmacokinetics as the mechanism responsible for loss of response to vedolizumab, nor do they support a need for higher drug concentration to enhance vedolizumab's immune effects. Higher pre-escalation levels may indicate less clearance [less severe disease] and higher likelihood of subsequent re-gained response, regardless of therapy escalation.